Collaborative Efforts in Family Health Management: The Contribution of Nursing, Social Work, Health Informatics, Health Administration, and Epidemiology - Omar Radhi Jodallah Alrehaili; Abdullah Ayed Alharbi; Ayed Aqeel Ayed Alanazi; Abdullah Mohammed Alassaf; Aiman Saleh Braiqea Alshammari; Hatim Sulaiman Hujhuj Alshammari; Majid Hamad Ali Al-Sanani; Abdulla Mohammed Al Wahaibi; Souad Abdullah Alaliwat; Turki Motlaq Almutiri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Family health management deals with all the health needs that are physical , emotional, social and environmental that may o Cupress within the units of a given family. Therefore, to enhance the different outcomes, there is a need to adopt team-based social models of care. Nursing, social work, health informatics, health administration and epidemiology integration is important. In each discipline, there is specialization which would help in the treatment of the diversified needs, that patients’ families present to the immediate care givers of patients, not forgetting that patient care takes time. Aim of work: To explore the contributions of Nursing, Social Work, Health Informatics, Health Administration, and Epidemiology to family health management, highlighting how their collective efforts improve health outcomes, empower families, and strengthen health systems. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Collaborative Efforts, Family Health, Management, Nursing, Social Work, Health Informatics, Health Administration, and Epidemiology. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Effective family health management can best be implemented through cooperation from the nursing, social work, health informatics, health administration, and epidemiology professions. Each course contributes specific perspectives and supports the multifaceted aspects of medical, social and natural conditions which affect a family’s health. In turn, such professionals develop an integrated model of practice that engages families, demonstrates the effectiveness of diversity, and improve health systems. Nonetheless, more work needs to be done in promoting investment in strategically modem and inter-professional service delivery model and training and education of professionals for better and holistic care for such families.